Lack of Epstein-Barr virus- and HIV-specific CD27- CD8+ T cells is associated with progression to viral disease in HIV-infection. - van Baarle, D; Kostense, S; Hovenkamp, E; Ogg, G; Nanlohy, N; Callan, M; Dukers, N; Mcmichael, A; van Oers, M; Miedema, F (2002)
OBJECTIVE: Despite readily detectable virus-specific CD8+ T cells in most HIV-infected patients, immune surveillance is eventually lost, leading to progression to AIDS. To investigate the underlying mechanism of this loss of immune control phenotypic analysis of HIV- and Epstein-Barr virus (EBV)-specific CD8+ T cells was performed. DESIGN: In three clinically distinct groups, long-term asymptomatics, progressors to opportunistic infections and progressors to EBV-associated non-Hodgkin lymphoma's (NHL), both number and phenotype of virus-specific CD8+ T cells was studied longitudinally. METHODS: The number of HIV- and EBV-specific T cells were determined using HLA-peptide tetrameric complexes. The phenotype of these virus-specific T cells was investigated by costaining with CD27 and CD45RO and thereby identifying specific subsets of CD8+ T cells. RESULTS: Individuals co-infected with HIV and EBV persistently had low numbers of HIV-specific CD27- T cells, in contrast to rising numbers of EBV-specific CD27- CD8+ T cells. However, HIV-infected individuals developing EBV-associated AIDS-related NHL had very low numbers of EBV-specific CD27- CD8+ T cells. Higher numbers of HIV-specific CD27- CD8+ T cells were associated with delayed disease progression. Virus-specific CD27- T cells, compared with CD27+ T cells showed elevated interferon-gamma production in response to viral peptides in vitro, indicative for strong effector function. CONCLUSIONS: Taken together, our data indicate that virus-specific CD27- T cells may be important effector T cells in controlling chronic viral infections in humans and that lack of differentiation into CD27- effector T cells may lead to progression of viral disease.